Using river sediments to analyze the driving force difference for non-point source pollution dynamics between two scales of watersheds. (1st August 2018) - Ouyang, Wei; Yang, Wanxin; Tysklind, Mats; Xu, Yixue; Lin, Chunye; Gao, Xiang; Hao, Zengchao
Abstract: The formation and transportation processes of non-point source (NPS) pollution varied among the studied watersheds in the Northeastern China, so we hypothesized that the driving force behind NPS pollution followed the spatial scale effect. With a watershed outlet sedimentary flux analysis and a distributed NPS pollution loading model, we investigated the temporal dynamics of NPS and the differences in driving forces. Sediment core samples were collected from two adjacent watersheds, the smaller Abujiao watershed and the larger Naoli watershed. The natural climatic conditions, long-term variations in the distribution of land use, soil properties and tillage practices were the same in the two watersheds. The vertical distributions of total nitrogen, total phosphorus, Zn and As at 1-cm intervals in the section showed clear differences between the watersheds. There were higher concentrations of total nitrogen and total phosphorus in the larger watershed, but the heavy metals were more concentrated in the smaller watershed. Lead-210 ( 210 Pb) analyses and the constant rate of supply model provided a dated sedimentary flux, which was correlated with the corresponding yearly loading of NPS total nitrogen and total phosphorus in the two watersheds. The total phosphorus showed a stable relationship in both watersheds with an R 2 value that ranged from 0.503 to 0.682. A rose figure comparison also demonstrated that the pollutant flux in the sediment was very different in the two watersheds, which had similar territorial conditions and different hydrological patterns. Redundancy analysis further indicated that expanding paddy areas had a large impact on the sedimentary flux of nitrogen and phosphorus in the smaller watershed, but precipitation had a direct impact on NPS loading in the larger watershed. We concluded that the spatial scale effect affected the NPS pollution via the transport processes in the waterway, which was mainly influenced by branch length and drainage density. Highlights: Similar territorial condition and pollution loads caused different sediment profile. Pollutants flux in sediment varied between two scales of watersheds. Redundancy analysis proved that different factors affected for pollution load between watersheds. Spatial scale affected the transport process and the resulting delivery of NPS pollution within each watershed.